PENGARUH INVESTMENT OPPORTUNITY SET,COLLATERAL ASSET,MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus Perusahaan Industri Barang Konsumsi Periode 2015-2019) - putri, annisa; Dillak, Vaya Juliana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effect of investment opportunity sets,collateral assets, managerial ownership, and institutional debt on dividendpolicy in consumer goods industrial sector companies listed on theIndonesia Stock Exchange for the 2015-2019 period. The technique used inthis research is purposive sampling. The samples obtained were 18 sampleswith a five year research period so that in this study 90 data were obtained.The method used was multiple linear regression analysis using SPSS 25software.The results show that simultaneously investment opportunity set,collateral asset, managerial ownership, and institutional ownership havean effect on dividend policy. While partially the investment opportunity sethas a positive effect on dividend policy, collateral assets have a negativeeffect on dividend policy, while managerial ownership and institutionalownership have no effect on dividend policy..